2008
DOI: 10.1002/cncr.23371
|View full text |Cite
|
Sign up to set email alerts
|

Frequent overexpression of Aurora Kinase A in upper gastrointestinal adenocarcinomas correlates with potent antiapoptotic functions

Abstract: BACKGROUNDUpper gastrointestinal adenocarcinomas are a common cause of cancer‐related deaths. In this study, the authors investigated the prevalence and biological significance of Aurora Kinase A (AURKA) overexpression in upper gastrointestinal adenocarcinomas.METHODSQuantitative real‐time polymerase chain reaction (qRT‐PCR) and immunohistochemical staining on tumor tissue microarrays (TMA) were used to study the expression of AURKA in upper gastrointestinal adenocarcinomas. To investigate the biological and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 39 publications
6
94
1
Order By: Relevance
“…This overexpression was more prevalent in gastroesophageal junction adenocarcinomas and lower in esophageal, Barrett-related adenocarcinomas (BAS) than in antrum and body gastric adenocarcinomas. They also found that the expression of AURKA caused an anti-apoptotic effect in gastrointestinal cancer cells with drug-induced apoptosis in an in vitro model (27). Rugge et al found that AURKA immunostaining increased significantly along with the Barrett's carcinogenesis, from Barrett's mucosa even without metaplasia towards Barrett's adenocarcinoma (24).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This overexpression was more prevalent in gastroesophageal junction adenocarcinomas and lower in esophageal, Barrett-related adenocarcinomas (BAS) than in antrum and body gastric adenocarcinomas. They also found that the expression of AURKA caused an anti-apoptotic effect in gastrointestinal cancer cells with drug-induced apoptosis in an in vitro model (27). Rugge et al found that AURKA immunostaining increased significantly along with the Barrett's carcinogenesis, from Barrett's mucosa even without metaplasia towards Barrett's adenocarcinoma (24).…”
Section: Discussionmentioning
confidence: 97%
“…AURKA protein levels and kinase activity are low in the G1/S phase; accumulate during G2/M and decrease rapidly following mitosis (25). AURKA is an important kinase-encoding gene involved in centrosome duplication and distribution; its overexpression leads to centrosome amplification, chromosomal instability and aneuploidy in several cancer types (26,27). AURKA overexpression has been found in numerous tumor cells and tissues including gastric cancer, breast cancer, colorectal cancer, bladder cancer, pancreatic cancer, ovarian cancer, prostate cancer and esophageal squamous-cell carcinoma, esophageal adenocarcinoma and Barrett's esophagus (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the samples, 70.0% (14/21) with AURK A amplification were poorly differentiated tumors and there was a statistically significant association between increased copy number of AURK A and tumor stages. Moreover, it is necessary to analyze AURK A amplification and its relation with expression levels in tumor samples because recent evidence (42) has shown the antiapoptotic potential of AURK A to gastrointestinal cells by regulating levels of P53 through the AKT/HDM2 pathway, and AURK A kinase inhibitors might be a therapeutic option for patients with AURK A-positive expression. An experimental study has shown that deletion of AURK A by AURK A-specific small interference RNA could be a potential therapeutic method in the treatment of gastric cancers (43).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies reported that there was a close association between Aurora-A overexpression and malignant biological behavior of cancer progression (9,16,(33)(34)(35). Additionally, Aurora-A overexpression was observed to be associated with egFr activation and overexpression (36,37).…”
Section: Carcinoma-specific Survivalmentioning
confidence: 99%